2021
DOI: 10.3390/vaccines9040393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thrombotic Adverse Reactions of COVID-19 AstraZeneca Vaccine Reported to EudraVigilance Database

Abstract: The development of safe, effective, affordable vaccines against COVID-19 remains the cornerstone to mitigating this pandemic. Early in December 2020, multiple research groups had designed potential vaccines. From 11 March 2021, several European countries temporarily suspended the use of the Oxford–AstraZeneca vaccine amid reports of blood clot events and the death of a vaccinated person, despite the European Medicines Agency (EMA) and the World Health Organization’s assurance that there was no indication that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 20 publications
0
60
0
Order By: Relevance
“…Furthermore, a study has shown that some vaccines (eg, Oxford-AstraZeneca) produce severe adverse effects, such as very rare blood clots and even fatalities. 38 Consequently, some countries, such as Denmark, have stopped using the Oxford-AstraZeneca vaccine. Our study found statistically significant differences in vaccine hesitancy between the vaccine preference subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study has shown that some vaccines (eg, Oxford-AstraZeneca) produce severe adverse effects, such as very rare blood clots and even fatalities. 38 Consequently, some countries, such as Denmark, have stopped using the Oxford-AstraZeneca vaccine. Our study found statistically significant differences in vaccine hesitancy between the vaccine preference subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Several rare but serious adverse reactions have been reported in the postmarketing surveillance of COVID-19 vaccines. For instance, according to a retrospective descriptive study using spontaneous reports submitted to the EudraVigilance database from 17 February to 12 March 2021, of the 54,571 adverse reactions to the AstraZeneca vaccine, 28 were thrombotic events [ 51 ]. In addition, during postauthorization use of the Janssen COVID-19 vaccine, thrombosis involving large blood vessels, including the cerebral venous sinuses, portal vein, lower extremity veins, and pulmonary artery, combined with thrombocytopenia, have all been reported [ 52 ].…”
Section: Post-authorization Experiencementioning
confidence: 99%
“…Following the 2009-10 H1N1 (swine flu) pandemic vaccination, four times as many women as men reported an allergic reaction to the H1N1 vaccine in the 20-59 age group [170] . In the case of COVID-19 vaccines, a severe adverse event seems to be plausibly related to AstraZeneca and Janssen vaccine administrations, namely the rare occurrence of thrombosis and thrombocytopenia mainly in women under 60 years [171] . EMA and AIFA recommended attention to prodromic symptoms of thrombosis in vaccinated individuals, and suggested to limit the use of these two vaccines to those over 60.…”
Section: Sex Differences In Response To Covid-19 Vaccinesmentioning
confidence: 99%